Integrating Quality by Design Principles for Elevating Bioavailability of Candesartan Cilexetil in Fast-dissolving Tablets (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: The present research was aimed to increase the bioavailability of Candesartan cilexetil by integratingefficient super disintegrating agents applying the principles of quality by design. Materials and Methods:This study optimized fast dissolving tablets containing Candesartan cilexetil by integrating efficient superdisintegrating agents (Isabgol husk, Potato starch, F melt C) through a direct compression method. Utilizing Designof Expert version 13.0 with a response surface methodology, formulations (CC1-CC15) were systematicallydeveloped. The influence of super disintegrates on key parameters - disintegration time (Y1), drug release at15 min (Y2), and drug release at 30 minutes (Y3) - was extensively studied to enhance Candesartan cilexetil’sdissolution properties. Results and Discussion: Comprehensive evaluation of pre- and post-compressionalfactors, coupled with robust in-vitro dissolution analysis, highlighted formulation CC12’s excellence, featuringrapid disintegration and maximal drug release within specified timeframes. Utilizing the DD solver guided byregression coefficients (r2), Akaike Information Criterion (AIC), and model selection criteria (MSC), kineticsand release mechanisms were elucidated. CC12 exhibited a fickian diffusion mechanism, substantiating itsrobust drug release profile. Additionally, shelf-life evaluation as per ICH guidelines and a comparative analysisemploying the similarity factor (f2) with Atacand were conducted. Stability studies, assessed via ANOVA,indicated insignificant differences (P > 0.05) during storage. In summary, this research optimally enhancedCandesartan cilexetil’s dissolution via proficiently formulated fast dissolving tablets. The strategic integrationof super disintegrating agents, driven by Design of Expert version 13.0, yielded CC12 as an optimal candidatewith rapid disintegration and superior drug release. Elucidation of release kinetics and mechanisms furtherfortified performance assessment. Thorough stability and similarity evaluations underscored the potential of thisoptimized formulation for improved therapeutic outcomes. Conclusion: Fast dissolving tablets of C and esartancilexetil were developed by optimizing selected independent variables to improve the dissolution profile. Thepresence of soluble polymers like Isabgol husk, potato starch and F melt C, acting as super disintegrants, playeda significant role in enhancing solubility.